Pengukuran Kinerja Mesin Milling CNC Mazak Variaxis 630/120 T V-5 Menggunakan Metode OEE Untuk Reduce Six Big Losses - Maksum Ardi, Hanni; Mulyadi, Yandi; Munir Fahmi, Mokhammad; Setiawan, Dibyo (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Machine performance is a key factor in maintaining productivity and efficiency in various industrial processes. Machines must be kept to ensure efficiency and optimal production capabilities. Therefore, machine performance measurement must be carried out to obtain results that can further improve machine reliability. The research was conducted in the aerospace industry and focused on one of the Mazak Variaxis 630/120 T V-5 CNC Milling machines. This research uses the overall equipment effectiveness (OEE) method, this method is an effective tool for determining and measuring machine performance. The OEE value that has been obtained then analyzes the six big losses in order to determine the losses that have the most impact on causing losses to the machine. The research results show that the average OEE value of this machine in a span of 1 year is 85.83% and meets the JIPM standard. The 2 losses obtained are idling and minor stoppages loss of 14.93% and reduced speed loss of 7.45%. Based on the fishbone analysis, it was found that the machine is a factor that greatly influences idling and minor stoppage loss and the human factor for reduced speed loss.